Nordic Vets against AMR—An Initiative to Share and Promote Good Practices in the Nordic–Baltic Region - Susanna Sternberg-Lewerin; Sofia Boqvist; Simen Foyn Nørstebø; Thomas Grönthal; Annamari Heikinheimo; Venla Johansson; Viivi Heljanko; Paula Kurittu; Nils Fall; Ulf Magnusson; Ane Mohn Bjelland; Henning Sørum; et al. (Antibiotics, 2022)
In the Nordic countries, antimicrobial use in animals and the prevalence of antimicrobial resistance are among the lowest in Europe. The network “Nordic Vets Against AMR” organized a meeting in 2021, with key actors including representatives from universities, veterinary authorities and veterinary organizations in Finland, Norway and Sweden. This paper reflects the most important discussions on education, research, policy and future perspectives, including the experiences of these countries. It concludes that Nordic veterinarians are well placed to lead the way in the fight against antimicrobial resistance and that the sharing of experiences can support colleagues in other countries. Veterinary education must go hand in hand with research activities and continuously updated guidelines and legislation. There is also a need for postgraduate training on antimicrobial resistance and prudent antimicrobial use. The veterinary profession must, by any means necessary, protect the efficiency of antimicrobials for the sake of animal health, animal welfare and productivity, as well as public health. While restrictive use of antimicrobials is crucial, the ability of veterinarians to use this medical tool is also important for the sake of animal welfare and global food security.